DESIGN OPTIMIZATION OF WAVEGUIDE FED DIPOLE APPLICATOR WITH INCLINED POLARIZATION PLANE - Zinkovskiy, Yu. F.; Sydoruk, Yu. K.; Turovskiy, A. O. (Radio Electronics, Computer Science, Control, 2014)
A design of microwave waveguide fed dipole applicator consisted of 5 elements for use in a device for bulk dielectric materials treatment with microwave electromagnetic field is proposed. In order to provide maximum amplitude and polarization homogeneity of the field distribution before the transmitter the main parameters of the design are calculated. Due to the dipoles being fully matched with feeding coaxial line segments the calculation of the whole structure is divided into internal and external problems. The influence of distance between the dipoles and waveguide’s surface on the width of the near field distribution pattern is shown and it is clarified that the reducing the distance will narrowing the field pattern. It was determined that the optimal zone location for placing of the bulk dielectric material to be irradiated is at the distance 100–150 mm from the dipoles.